Analisis Manajemen Logistik Tepung Tapioka (Studi Kasus Pada PD. Semangat Jaya) - Intan Anisa Putri; Zainal Abidin; Lina Marlina (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
This study aims to analyze delivery time, the percentage of logistics costs to product prices, and inventory management. This research is a case study at PD Semangat Jaya of Pesawaran District, Lampung Province. Data for this research was collected from November to December 2022.  Objectives 1 was analyzed using OTIF (On time in Full) method.  Objective was analyzed using data tabulation.  While objective 3 was analyzed using FIFO (First in First Out) approach.   Respondents in this study consisted of 1 owner, 1 field supervisors, and 1 administrative staff. The study suggests that the delivery time for tapioca flour from June to November started from 77.77% to 100%, so that the average delivery time for tapioca flour delivery to a trading company (PD.  Semangat Jaya) was 85.88%, which was consider to be good. for the delivery of a product.  The percentage of logistics costs for sending tapioca starch varies in each region, ranging from 33.26% to 33.46%, so that the average logistics cost is 33.33% of the selling price of tapioca flour.  The value of the final inventory of tapioca flour for one year in this company is Rp. 24,979,500,000.00.